A New Philosophy in Adaptive Control Design for Robust Attitude Maneuver of Spacecrafts. Issue 1 (2016) - Simha, Ashutosh; Padhi, Radhakant
Abstract: An adaptive control law has been designed for robust attitude tracking of a spacecraft with uncertain inertia matrix, torque coupling coefficients and exogenous disturbances. The strict block feedback structure of the attitude dynamics is exploited in designing a back stepping control law, which depends on a compensator variable whose dynamics is designed to adapt to the unknown parameters. Two switching components have been incorporated into the dynamic feedback law to ensure robustness with respect to the disturbances and uncertainties in the torque coupling coefficients. The spacecraft dynamics is simulated using the dynamic feedback control, first without the switching components and later incorporating the same, in order to demonstrate the effectiveness and robustness of the proposed method.